2018
DOI: 10.1080/09638288.2018.1434689
|View full text |Cite
|
Sign up to set email alerts
|

The Social Provisions Scale: psychometric properties of the SPS-10 among participants in nature-based services

Abstract: After modifications the scale showed not only satisfying psychometric properties, but it also clarified uncertainties regarding construct validity of the measure. However, further analysis on larger samples are required. Implications for Rehabilitation Social support is important for a variety of rehabilitation outcomes and for different patient groups in the rehabilitation context, including people with mental health or drug-related problems. Social Provisions Scale may be used as a screening tool to assess s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…These percentages are almost doubling those reported in Lee et al’s [ 47 ] study (i.e., 19.7% and 6.1%, respectively). In addition, more respondents (11.5%) in our study reported possible severe mental illness than among Caucasians (8.2%), Hispanics (9.3%), African Americans (10.3%) and Asian Americans (6.0%), as reported by Prochaska et al [ 49 , 44 ]. Furthermore, when compared to Lau [ 7 ] and Choi [ 6 ]’s studies, a significant higher percentage of people living in vulnerable families reported psychological distress during the COVID-19 epidemic.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These percentages are almost doubling those reported in Lee et al’s [ 47 ] study (i.e., 19.7% and 6.1%, respectively). In addition, more respondents (11.5%) in our study reported possible severe mental illness than among Caucasians (8.2%), Hispanics (9.3%), African Americans (10.3%) and Asian Americans (6.0%), as reported by Prochaska et al [ 49 , 44 ]. Furthermore, when compared to Lau [ 7 ] and Choi [ 6 ]’s studies, a significant higher percentage of people living in vulnerable families reported psychological distress during the COVID-19 epidemic.…”
Section: Discussionsupporting
confidence: 79%
“…Items are rated on a 4-point Likert scale (1 = strongly disagree to 4 = strongly agree). A Cronbach’s α of 0.75 has been reported for this scale [ 44 ], indicting adequate reliability. The Chinese version of the SPS has been used in Chinese communities by Li et al [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the cross-cultural equivalence of the PSS-10 (see [57,74]), the SPS, short form of PSP-10 [47] and the coronavirus concern scale (self-reported measure, constructed for the purpose of this study) prior to any main analyses. Using a multi-group factor analysis, we compared the models assuming the one-factor structure for SPS and coronavirus concerns, and the two-factor structure for PSS-10 ( positive and negative, with the latter consisting of reversed items; [75,76]) across all countries (configural invariance), with a model with factor loadings and latent correlations constrained to be equal (metric invariance), and items' intercepts to be the same in all groups (scalar invariance).…”
Section: Analysis Plan 91 Measurement Invariance Testingmentioning
confidence: 99%
“…In contrast, Steigen & Bergh found shortcomings in the SPS-10 related to targeting and construct validity using the polytomous Rasch model. 28 An alternate 10-item version of the SPS that measures each subscale with the two negatively worded statements has also been developed to better represent the lack of social support, but does not appear to be widely implemented. 29 In this paper, we refer to the SPS-10 as the version with positively worded items developed by Caron.…”
Section: Introductionmentioning
confidence: 99%